IMPACT OF PRICE, PRODUCT QUALITY, CORPORATE IMAGE ON CUSTOMER LOYALTY (MEDIATED BY SATISFACTION) AT SHELL FUEL STATIONS IN JAKARTA - Christopher, Darrell; Ruslim, Tommy Setiawan (International Journal of Application on Economics and Business, 2025)
In this study, price, product quality, and corporate image were examined for their influence on customer satisfaction and loyalty. The study focused on customers of Shell gas stations in Jakarta, involving 216 samples. The data collected through a questionnaire instrument (G-form) was analyzed by the researcher using SmartPLS4 software. It was found that all exogenous variables in this study influenced satisfaction and loyalty. Customer satisfaction also proved to be an important mediator in the relationship between all exogenous variables and loyalty in the gas station sector in Jakarta. Additionally, the study results showed that price and product quality had a direct positive impact on loyalty. However, corporate image was found to have a negative but insignificant effect on loyalty, indicating that while a positive image plays an important role, this factor does not directly determine loyalty without the support of competitive and consistent pricing and product quality. Beyond its contribution to academic literature, this study provides practical insights for Shell regarding the importance of fair pricing strategies and the delivery of appropriate product quality to enhance satisfaction and sustain loyalty. On the other hand, corporate image requires a more strategic, integrated, and sustainable approach to strengthen long-term relationships with customers.